Performance Analysis of Credit Unions in Lithuania - Kėdaitis, Vytautas; Girčytė, Justina (Lithuanian Journal of Statistics, 2015)
The paper deals with the assessment of the performance of Lithuanian credit unions applying a cluster analysismethod, in particular the Probit regression model, substantiates their relevance and reliability for the evaluation of the resultsobtained, checks the model stability taking into account the time lag, assesses the relevance of the model for the performance analysisof Lithuanian credit unions.
Keywords: credit unions; cluster analysis; Probit regression analysis; efficiency; estimation